Nutrient limitation bioassays using natural populations of Gephyrocapsa huxleyi from the Gulf of Aqaba in contrasting seasons - Keuter, Sabine; Frada, Miguel J; Koplovitz, Gil; Ben Yehouda, Mayaan (PANGAEA, 2025)
To disentangle the effect of macronutrient availability on cell-size in native populations of coccolithophores we surveyed the seasonality of the prevalent coccolithophores in the northern Red Sea and the Eastern Mediterranean and performed a series of incubations assays. For bioassays in stratified season and during winter mixing water samples were taken from 2 m depth off the pier of the IUI in Eilat (29.501735 N, 34.917801 E) and incubated at in situ temperature for 48 hours. 1 µM NaNO3 or/and 0.0625 µM of Na2 b-glycerophosphate were added to test for nutrient limitations in the Gulf of Aqaba. Scanning electron microscopy was used for coccolithophore enumeration and eukaryotic microalgae cells were identified and counted based on cell size scatter signals and red (chlorophyll) fluorescence using flow cytometry.
Keywords: Emiliania huxleyi; Field experiment; incubation experiment